PENGARUH METODE INDEX CARD MATCH TERHADAP KETERAMPILAN MEMBACA SISWA KELAS II SD NEGERI 2 TIJUE - Nanda Saputra (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2018)
This study aims to determine the effect of reading skills by using the index card match method for second grade students at SDN 2 Tijue, Pidie District. The population in this study were all students of second grade at SDN 2 Tijue. The number of the students were 50 while the samples in this study were class II as many as 50 students. The result of the study showed t count > t table. The result was 2,655 > 1,711 and df 48. It showed that there was an effect of the index card match method on reading skills of at second grade students in Pidie District.